2007
DOI: 10.1037/0033-2909.133.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, anxiety disorders, tobacco use, and nicotine: A critical review of interrelationships.

Abstract: Smoking is highly prevalent across most anxiety disorders. Tobacco use increases risk for the later development of certain anxiety disorders, and smokers with anxiety disorders have more severe withdrawal symptoms during smoking cessation than smokers without anxiety disorders. The authors critically examined the relationships among anxiety, anxiety disorders, tobacco use, and nicotine dependence and reviewed the existing empirical literature. Future research is needed to better understand the interrelationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
234
4
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(265 citation statements)
references
References 330 publications
(476 reference statements)
10
234
4
17
Order By: Relevance
“…These data add to the growing theoretical and empirical literature suggesting that smokers with anxiety disorders may benefit from specialized treatment approaches that target these anxiety factors for the purpose of more effectively preventing relapse (Morissette et al, 2007;Zvolensky & Bernstein, 2005). Indeed, from a clinical perspective, the combination of a potentially increased reliance on smoking as a method of coping with the experience of negative mood and diagnosis-specific symptoms accompanied by a particularly pronounced experience of symptoms during quit attempts may help explain why these individuals are a difficult-to-treat sub-population of smokers.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These data add to the growing theoretical and empirical literature suggesting that smokers with anxiety disorders may benefit from specialized treatment approaches that target these anxiety factors for the purpose of more effectively preventing relapse (Morissette et al, 2007;Zvolensky & Bernstein, 2005). Indeed, from a clinical perspective, the combination of a potentially increased reliance on smoking as a method of coping with the experience of negative mood and diagnosis-specific symptoms accompanied by a particularly pronounced experience of symptoms during quit attempts may help explain why these individuals are a difficult-to-treat sub-population of smokers.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have found important linkages between smoking and certain anxiety disorders (Feldner, Babson, & Zvolensky, 2007a;Morissette, Tull, Gulliver, Kamholz, & Zimering, 2007;Patton, Carlin, Coffey, Wolfe, Hibbert, & Bowes, 1998; Zvolensky, Feldner, LeenFeldner, & McLeish, 2005 (Beckham et al, 1995;Breslau et al, 2003;Buckley et al, 2004;Feldner et al, 2007a). Recent controlled work supports the contention that PTSD is associated with earlier relapse compared to persons with no psychopathology (Zvolensky, Gibson et al, in press).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In the striatum, modulation of dopamine release by nAChRs may affect symptoms as well as the pathological degeneration of the dopaminergic neurons in Parkinson's disease [53]. Interest in nicotinic regulation of the dopamine system has also been stimulated by the observations that some of nicotine's effects on learning and memory [54,55], anxiety [56,57] and locomotor activation [58,59] may result as a consequence of dopamine release. Additional interest in nAChR-dopamine interactions comes from the observations that individuals suffering from dopamine-related psychopathologies such as schizophrenia and attention deficit hyperactivity are frequently smokers (incidence > 50-60%) [60,61] and that smoking may retard the onset of Parkinson's disease [62].…”
mentioning
confidence: 99%
“…Level two of the model accounted for an additional 5% of the variance, with the appetite control subscale being the only significant predictor (β = −.16, p < .05). There is a recent and increasingly well-documented association between cigarette smoking and depressive and anxiety symptoms and disorders (Morrell & Cohen, 2006;Morissette, Tull, Gulliver, Kamholz, & Zimering, 2007;Patton, Carlin, Coffey, Wolfe, Hibbert, & Bowes, 1998). Indeed, epidemiological (Grant, Hasin, Chou, Stinson, & Dawson, 2004;Lasser, et al, 2000), community (Hayward, Killen, & Taylor, 1989) and clinical (Himle, Thyer, & Fischer, 1988;McCabe et al, 2004;Pohl, Yeragani, Balon, Lycaki, & McBride, 1992) studies have found that daily cigarette smoking is more common among those with anxiety and depressive psychopathology compared to those without such problems.…”
mentioning
confidence: 99%